Optimizing an Enhanced Recovery Pathway Program: Development of a Postimplementation Audit Strategy. - Grant, Michael C.; Galante, Daniel J.; Hobson, Deborah B.; Lavezza, Annette; Friedman, Michael; Wu, Christopher L.; Wick, Elizabeth C. (Joint Commission Journal on Quality & Patient Safety, 2017)
Background Enhanced recovery pathways (ERPs) are bundled best-practice process measures associated with reduction of preventable harm, decreased length of stay (LOS), and increased overall value of care. An auditing procedure was developed to assess compliance with 18 ERP process measures and establish a system for identifying and addressing defects in measure implementation. Methods For a one-year period, the electronic health records of 413 consecutive patients treated on a multidisciplinary ERP for colorectal surgery at an academic medical center were evaluated with the audit procedure. Patients were stratified who both met the expected LOS, as defined by LOS less than the historical (pre-ERP) average LOS for the same procedure ("successes"), and exceeded the historical LOS ("outliers"). On the basis of the results of the audit process, a number of system-level interventions were developed. The results were then assessed for a three-month follow-up period to determine the impact on process measure compliance and LOS. Results Detailed review of outliers identified several defects that improved following implementation of system-level changes, such as early mobility after surgery (44.4% vs. 59.5; p = 0.02). Although increased compliance through selective process measure optimization did not lead to a significant reduction in overall LOS (days; 5.2 ± 5.0 vs. 4.9 ± 3.0; p = 0.37), the audit procedure was associated with a significant reduction in outliers' LOS (days; 12.2 ± 6.8 vs. 9.0 ± 2.1; p = 0.03). Conclusion Concentrating audits in patients who fail to meet expectations on an ERP is an effective strategy to maximize identification of defects in and improve on pathway implementation.